Geomorphological and glaciological aspects around the highest dome in Queen Maud Land, East Antarctica - Ageta, Yutaka; Kaminuma, Kokichi; Okuhira, Fumio; Fujii, Yoshiyuki (National Institute of Polar Research, 1989)
P(論文) The oversnow traverse party of the Japanese Antarctic Research Expedition in 1985 found the location of the top of the second highest dome in the Antarctic Ice Sheet at 77°22'S, 39°37'E with an elevation of 3807 m, and surveyed the dome. A ridge of the ice divide runs from the dome top in a west-northwest direction, and a narrow subsurface basin lower than 500 m above the sea-level extends in a scale of 100 km long below the dome top in a similar direction to that of the surface ridge. In view of the larger scale of 100 km order on the subsurface topography, this dome is classified into "the subglacial basin type" in contrast with "the subglacial mountain type" such as Dome A, the highest dome in the Antarctic Ice Sheet. Comparative study between such types is important for discussions on the formation, development and variation of the ice sheet in the geological time scale, as well as their dynamics. From climatological and glaciological observations around the dome, the directions of prevailing winds and the lapse rates of snow temperature at 10 m depth (annual mean air temperature) are described, and the effect of the surface slope on such surface environments is discussed briefly. Annual mean air temperature at the dome top is estimated to be -58.0℃. By the use of mean annual net accumulation of 3.2 cm in water equivalent which was abtained from the 5 m-pit profile of tritium content near the dome top, age of the dome ice with depth is simply estimated. departmental bulletin paper